1970
DOI: 10.1107/s0021889870006805
|View full text |Cite
|
Sign up to set email alerts
|

The microstructure of PAN-base carbon fibres

Abstract: The microstructure of polyacrylonitrile-base (PAN-base) type I and type II carbon fibres has been studied by X-ray small-angle and wide-angle scattering. Recent work in this field is critically reviewed and it is shown that the structural model proposed by Johnson & Tyson for these types of fibre is inadequate. The microstructure of PAN-base carbon fibres is essentially the same as that of rayon-base carbon fibres. Differences appear only in the volume fraction occupied by the microvoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(90 citation statements)
references
References 0 publications
6
84
0
Order By: Relevance
“…SAXS studies on bundles of carbon fibers have also been reported by Perret & Ruland (1970). Two types of intensity measurements were selected: intensity measurements perpendicular to the fiber axis with an infinitely long slit (Kratky camera) parallel to the fiber axis, shown schematically on the left-hand side of Fig.…”
Section: Introductionmentioning
confidence: 99%
“…SAXS studies on bundles of carbon fibers have also been reported by Perret & Ruland (1970). Two types of intensity measurements were selected: intensity measurements perpendicular to the fiber axis with an infinitely long slit (Kratky camera) parallel to the fiber axis, shown schematically on the left-hand side of Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The radius of the rod-like flowinduced structures can thus be obtained as ðR c Þ 1=2 and is about 30 nm. The length L of the rod-like flow-induced scatterers can be calculated using Ruland's model (Perret & Ruland, 1969, 1970Ruland, 1969), according to which the azimuthal breadth of the equatorial streak (B obs ) is the sum of a contribution arising from the finite size of the scatterers (1/Ls) and a contribution arising from object misalignment (B or ): Polymer crystallization studies at DUBBLE 1687 Figure 7 Two-dimensional SAXS images of i-PP crystallized after the application of a shear pulse and at different apparent wall stresses. For w = 0.19 MPa, the best fit of the Ruland model suggests that the average length of the scatterers is about 290 nm (Fig.…”
Section: Shear-induced Crystallization Using a Slit Rheometermentioning
confidence: 99%
“…Further, Lc is dependent on the orientation of the crystallite, and this dependency is emphasized at higher carbonization temperatures. Larger crystallite dimensions of the more-aligned domains have been reported earlier [25], and has ben attributed to the smaller thickness of misaligned graphitic planes that interlink the more-aligned domains in the ribbon model. It is also possible that enhanced crystallite growth of the aligned domains, caused by the existing preferential orientation of molecules in the stabilized fiber, results in orientation-dependent crystallite size.…”
Section: Results From Wide-angle X-ray Diffraction Studiesmentioning
confidence: 74%